WILINESS TO PAY: AZOREAN ETHNOCENTRIC BUYER BEHAVIOR - Vieira, Maria João; Tiago, Teresa; Tiago, Flávio (European Scientific Journal, ESJ, 2014)
The increasing emphasis on the disclosure of the national and regional brands contributed in a significant way to the creation of new launch campaigns and stimulation of what the country and region has to offer. Therefore, in the literature it can be found numerous references to the influence of ―country-of-origin‖ in products sales. Less acknowledge is the influence of a specific region. However, when you have regions with financial and political autonomy, it‘s expectable that efforts are made to promote in a differentiate mode the local products. And both academic and firms expected that these investments would influence the ―region of origin‖ effect on regional buyers and decreases their price sensibility regarding local products. This is because understanding the influence of the ―Azorean brand‖ in the imaginations of the consumers, and the ethnocentricity of their behaviors, are directly related with the regional economic expansion. Knowing the clients‘ WTP toward Azorean products leads to an increase of new products and further stimulates the development of the local market. In this framework in mind, data was collected covering the CETSCALE dimensions and the WTP elements for grocery products. The results show the existence of three different patterns of ethnocentricity in Azorean consumers, as well as demonstrate that for most products ―region of origin‖ is not a strong influencer of wiliness to pay. Considering that the current research reflects different categories of Azorean products, the conclusions are general in nature, and conditioned according to the respondents‘ answers. This limitation can be seen as an opportunity for a more detailed research of consumers‘ behavior regarding different categories of regional products.